Descriptions of species of Acrobeles von Linstow, 1877 (Nematoda, Rhabditida, Cephalobidae) from Kelso Dunes, Mojave National Preserve, California, USA - Boström, Sven; Holovachov, Oleksandr (Zootaxa, 2019)
Populations of three rare species of the genus Acrobeles are described from the Kelso Dunes area, Mojave National Preserve, southern California. One population is identified as belonging to A. undulatus and is compared with the type population from Venezuela and one population from Iran. Males of this species are described for the first time. Another population identified as belonging to A. ornatus is compared with the type population from Colorado, USA. Specimens identified as belonging to A. dimorphus are compared with the type population from Namibia. Descriptions of the new material add morphological data important for species identification, broaden the diagnosis of Acrobeles and increase the distribution patterns of these three species.